Acupoint selection rules in treatment of cancer with moxibustion☆灸法用于癌症治疗的选穴规律分析 - PAN(潘茹芳), Ru-fang; MA(马舒雅), Shu-ya; GAO(高田宇), Tian-yu; ZHANG(张飞程), Fei-cheng; LI(李天玉), Tian-yu; JIA(贾春生), Chun-sheng; PAN(潘丽佳), Li-jia (World journal of acupuncture-moxibustion, 2024)
To summarize the rules of acupoint selection in treatment of cancer with moxibustion by analyzing the articles of relevant clinical trials in recent years in China, so as to provide the references for acupoint selection of moxibustion for cancer. The articles of clinical trials for treatment of cancer with moxibustion were retrieved from China National knowledge Infrastructure (CNKI), VIP Chinese Journal Service Platform (VIP) and Wanfang Data Knowledge Service Platform (Wanfang) from 1st January 2015 to 30th June 2021. Using EpiData software, the data were extracted and exported in Excel. The analysis was performed with IBM SPSS Statistics 23 software. A total of 516 articles were collected, including 533 prescriptions with 164 acupoints involved. The high-frequency acupoints were similar among 7 types of cancers and these acupoints mostly acted on supporting the antipathogenic qi, replenishing qi and regulating the spleen and stomach. Regarding meridian tropism, the acupoints from the conception vessel, the governor vessel and bladder meridian were dominant in treatment of cancer with moxibustion. In terms of location distribution, the selected acupoints were generally distributed on the chest, abdomen, lumbar region and the upper back of the body. Based on cancer related symtomes in different systems, the use frequency of Zusanli (ST36) was the highest for the symptoms of the immune, digestive, circulatory and motor systems; that of Feishu (BL13) was the highest for the respiratory system symptoms and that of Guanyuan (CV4) was the highest for the urinary system symptoms. The cluster analysis of high-frequency acupoints showed that the acupoints of moxibustion for cancer generally work on cultivating yang, supporting the antipathogenic qi, strengthening the spleen and harmonizing the stomach, and were selected in association with the clinical symptoms of different cancers. In treatment of cancer with moxibustion, the acupoints of the conception vessel and the governor vessel, as well as the back-shu points of the bladder meridian were dominated. All of these acupoints acted on supporting the antipathogenic qi, replenishing qi and regulating the spleen and stomach. It emphasized the etiology of “the deficiency in the root” of cancer, and the characteristics of acupoint selection based on syndrome differentiation in treatment with moxibustion.